Representation of Banyumas Local Wisdom Values Reflected in the Kembang Glepang Anthology - Abdul Wachid Bambang Suharto; Aufannuha Ihsani; Teguh Trianton; Kim Young Soo (Indonesian Academy of Social and Religious Research (IASRR), 2026)
This article aims to reveal the representation of Banyumas local wisdom values ​​as reflected in the Kembang Glepang anthology. Researchers interpreted data related to the value of local wisdom in the literary works of Banyumas writers in the Kembang Glepang anthology. The data in the research were obtained from interviews, observations and interpretations of the literary works of Banyumas writers in the anthology Kembang Glepang. The focus of this research is on the book Kembang Glepang which was used by the Culture and Tourism Service as an effort to explore literacy in Banyumas. Representations of Banyumas local wisdom values ​​as reflected in the Kembang Glepang anthology appear in art, language and discourse. In Banyumas, traditional art reflects local wisdom in various aspects, from themes, styles, to the techniques used. Art plays a crucial role in preserving local wisdom amidst the currents of globalization and modernization. Then what is more important is the linguistic aspect. The Kembang Glepang anthology contains various aspects of linguistic locality which make this anthological work unique. This linguistic aspect is concluded in the use of Banyumasan terms and proverbs in the various literary works published, the existence of local legends that inspired the birth of folklore, the use of certain ritual language in literary works, the existence of place names and people's names that symbolize Banyumasan, and the use of dialects. as well as language variations in narrative, dialogue, or in the poetry of the Kembang Glepang anthology. For the people of Banyumas, the ngapak dialect is not just a means of communication, but also a symbol of cultural identity.